2008
DOI: 10.2337/dc07-1457
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Tyrosine Phosphatase Nonreceptor 22 (PTPN22) Is Associated With High GAD Antibody Titer in Latent Autoimmune Diabetes in Adults

Abstract: OBJECTIVE -We previously demonstrated the presence of two different populations among individuals with adult-onset autoimmune diabetes: those having either a high titer or a low titer of antibodies to GAD (GADAs). Protein tyrosine phosphatase nonreceptor type 22 (PTPN22) has been identified as a new susceptibility gene for type 1 diabetes and other autoimmune diseases. The aim of the present study was to evaluate whether the phenotypic heterogeneity of adult-onset autoimmune diabetes based on the GADA titer is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
42
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 24 publications
(30 reference statements)
4
42
2
1
Order By: Relevance
“…In detail, patients with higher anti-GAD65 titres can be described by a more profound autoimmunity, quite marked dependency on insulin, higher levels of serum A1C, and lower both body mass index (BMI) and metabolic syndrome prevalence and, regarding genetic traits, decreased frequency of HLA-DRB1*0403 and HLA-DQB1*0602 and an increased for HLA-DRB1*03 and HLA-DQB1*0201 characterises the patients with higher anti-GAD65 titres [39] . Furthermore, studies from the same nationwide survey revealed that in LADA, the variant PTPN22 1858T is strongly associated with high titres of anti-GAD65 autoantibodies while the low levels are correlated to the T2D genetic variant of susceptibility, TCF7L2 [40,41] . It has also been suggested that the presence of high anti-GAD65 titres and/or anti-GAD65 autoantibodies directed against the C-terminal and not the middle epitopes of the protein can group a LADA subphenotype with many similarities with classic T1D and a high probability to develop insulin deficiency [42] .…”
Section: At Thementioning
confidence: 99%
“…In detail, patients with higher anti-GAD65 titres can be described by a more profound autoimmunity, quite marked dependency on insulin, higher levels of serum A1C, and lower both body mass index (BMI) and metabolic syndrome prevalence and, regarding genetic traits, decreased frequency of HLA-DRB1*0403 and HLA-DQB1*0602 and an increased for HLA-DRB1*03 and HLA-DQB1*0201 characterises the patients with higher anti-GAD65 titres [39] . Furthermore, studies from the same nationwide survey revealed that in LADA, the variant PTPN22 1858T is strongly associated with high titres of anti-GAD65 autoantibodies while the low levels are correlated to the T2D genetic variant of susceptibility, TCF7L2 [40,41] . It has also been suggested that the presence of high anti-GAD65 titres and/or anti-GAD65 autoantibodies directed against the C-terminal and not the middle epitopes of the protein can group a LADA subphenotype with many similarities with classic T1D and a high probability to develop insulin deficiency [42] .…”
Section: At Thementioning
confidence: 99%
“…In their LADA patients, they confirmed an increased frequency of type 1 diabetes-associated genetic risk factors including the heterozygous HLA-DQB1*0201/*0302 genotype, insulin AA genotype (rs689), and increased CT and TT genotypes of the PTPN22 gene (rs2476601) (2). Somewhat surprisingly, in LADA patients they also found a higher frequency of the type 2 diabetesassociated CT and TT genotypes of the TCF7L2 gene (rs7903146) (3), therefore concluding that LADA shares genetic features with both type 1 and type 2 diabetes.…”
mentioning
confidence: 82%
“…A series of papers over the past decade has shown that individuals with LADA share the HLA, insulin gene and PTPN22 variant associations that are characteristic of type 1 diabetes [8,9,12,24]. These findings establish that the islet autoimmunity of LADA is causal (rather than secondary to exposure to antigens released from islet cells destroyed by other processes).…”
mentioning
confidence: 96%
“…With the recent crop of genome-wide association studies taking the tally of loci confidently implicated in the pathogenesis of multifactorial forms of diabetes [3][4][5] to more than 60, it has become possible to use these to explore the 'aetiological architecture' of diabetes. A number of recent papers describe attempts to do just this [6][7][8][9][10][11][12][13][14].…”
mentioning
confidence: 99%
See 1 more Smart Citation